2021
DOI: 10.3390/catal11080931
|View full text |Cite
|
Sign up to set email alerts
|

Cascading Old Yellow Enzyme, Alcohol Dehydrogenase and Glucose Dehydrogenase for Selective Reduction of (E/Z)-Citral to (S)-Citronellol

Abstract: Citronellol is a kind of unsaturated alcohol with rose-like smell and its (S)-enantiomer serves as an important intermediate for organic synthesis of (-)-cis-rose oxide. Chemical methods are commonly used for the synthesis of citronellol and its (S)-enantiomer, which suffers from severe reaction conditions and poor selectivity. Here, the first one-pot double reduction of (E/Z)-citral to (S)-citronellol was achieved in a multi-enzymatic cascade system: N-ethylmaleimide reductase from Providencia stuartii (NemR-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…On the one hand, the supplement of exogenous NADP + significantly increased the catalytic efficiency, and the NADP + concentration (>0.4 mM) was required to maintain high catalytic activity (Figure S5a). On the other hand, the addition of FMN did not increase the conversion (Figure S5b), suggesting that the binding of FMN was tight enough for maintaining the activity of the variant S296/W116G [36]. In addition, the amounts of GDH and glucose were important for the efficiency of NADPH regeneration.…”
Section: Asymmetric Synthesis Of (R)-citronellal and Simultaneous Resolution Of (E)-citral And (Z)-citral Catalyzed By The Oye3 Variant Smentioning
confidence: 97%
“…On the one hand, the supplement of exogenous NADP + significantly increased the catalytic efficiency, and the NADP + concentration (>0.4 mM) was required to maintain high catalytic activity (Figure S5a). On the other hand, the addition of FMN did not increase the conversion (Figure S5b), suggesting that the binding of FMN was tight enough for maintaining the activity of the variant S296/W116G [36]. In addition, the amounts of GDH and glucose were important for the efficiency of NADPH regeneration.…”
Section: Asymmetric Synthesis Of (R)-citronellal and Simultaneous Resolution Of (E)-citral And (Z)-citral Catalyzed By The Oye3 Variant Smentioning
confidence: 97%
“…WZY002), and BmGDH M6 (from Bacillus megaterium) to catalyze the biotransformation of (E/Z)-citral to (S)-citronellol. 57 Due to limited cell capacity, the expression level of BmGDH M6 is reduced in coexpressed bacteria, resulting in insufficient activity to meet the requirements of two reductases. After 24 h of reaction, feeding additional wet cells expressing BmGDH M6 achieved a complete substrate conversion of up to 400 mM.…”
Section: Terpenoid Flavormentioning
confidence: 99%
“…The cell envelope offered the protection of intracellular enzymes but also the permeability of hydrophobic substrates to keep the reaction going. [35][36][37] Compared with isolated enzymes, the use of whole-cell catalysts could simplify the procedure of biocatalyst preparation and facilitate the biocatalyst reuse, offering a cost-effective advantage. More importantly, further catalytic experiments revealed that the e.e.…”
Section: Whole-cell Catalyzed Hydrolysis Of D L-menthyl Acetate To L-...mentioning
confidence: 99%